Enfermedad de Rosai-Dorfman extranodal: presentación de un caso con afectación intracraneal aislada - Sáenz, Leslie; Oleaga, Laura; Berenguer, Joan (Revista del Hospital Italiano de Buenos Aires, 2013)
-